DEVELOPMENT OF AN ENTREPRENEURSHIP SOUL TRAINING MODEL FOR UNIVERSITAS BRAWIJAYA'S STUDENTS - Mawardi, Mukhammad Kholid; Muslim, Abdul Qadir; Setyono, Langgeng; Praja, Bayu Amengku (Erudio Journal of Educational Innovation, 2024)
Human capital theory argues that if someone is given education, in the future their work productivity will develop, because someone has the knowledge and skills to carry out their work better. The nation's literacy rate has increased. Based on 2016 BPPS data, the imbalance between job opportunities and the workforce in Indonesia means that intellectual unemployment is increasing. A shift in the education system is needed, namely not producing graduates who are solely looking for job opportunities, but rather graduates who are oriented towards job creation, namely entrepreneurship and campaigning for the promotion of entrepreneurship in the PT world. Based on this, this research is very important to carry out because it will help reduce the number of educated unemployed, especially in the UB Vocational Faculty. Graduates do not only choose to become civil servants and formal jobs, but can become entrepreneurs to build the nation and state. Therefore, the researchers took the title "Development of an Entrepreneurship Spirit Training Model for Undergraduate Students: Solutions for Planning Future Careers". The objectives of this research are: 1) Identifying the needs for training in the entrepreneurial spirit of UB Vocational Faculty students. 2) Create a training model for the entrepreneurial spirit of UB Vocational Faculty students. And 3) Create a Spirit of Entrepreneurship training package for UB Vocational Faculty students. This research, both the first and second year, used the Borg & Gall model development research approach (1983:775). Research in Year I, step 1 The research team conducted a preliminary study to photograph the student training model which was continued in Year II, namely creating an entrepreneurship training package. The research team developed 2 versions of the training model in consultation with experts, then the product was revised. Small-scale and large-scale trials were carried out by the Research Team, so that in the end a final entrepreneurial spirit training model was obtained. This product is used as the basis for creating an entrepreneurial spirit training package. This entrepreneurship training model can be used after the entrepreneurial spirit training package (theme, objectives, modules/materials, schedule, place, presenters, participants, rules, etc.) has been created as a complement to organizing student entrepreneurial spirit training.